La ablación en la comunidad indígena embera chami-preponderancia de derechos (2014)
The main objective of the thesis is to consolidate respect for ethnic minorities in Colombia, so the effectiveness of legal protection is analyzed them versus ablation Embera Chami community.   Epistemologically, the research addresses historical, psychological, sociological and legal elements of the subject matter, ie, the phenomenon develops circumstances. Embera Chami tribe, who inhabited Pueblo Rico Risaralda, Gito Dokabu Indian reservation, through testimony and reconnaissance, to analyze this problem is analyzed. Therefore, this research is descriptive, with a socio-legal, court analytical and deductive method, you need a qualitative approach, and primary and secondary sources will interview the Municipal Representative of Pueblo Rico Maria Piedrahita Bermudez laws, case law and national and international standards